Pianists interpretive insights: exploring hunt, military and pastoral motifs through Monelles topic theory - Ding, Jin (Tanjong Malim, 2024)
Pianists interpretive insights: exploring hunt, military and pastoral motifs through Monelles topic theory by Ding, Jin